Medo de cair em idosos com e sem diabetes mellitus: estudo conduzido em idosos da comunidade e da Rede FIBRA - Bruno de Souza Moreira (2017)
Diabetes mellitus is a very prevalent health condition, particularly among older adults. This metabolic disease has deleterious effects on multiple organ systems, which combined with the natural aging process favor the occurrence of adverse outcomes, such as falls and fear of falling. Fear of falling is a common and potentially disabling problem in the elderly population, which is present even in older adults without a history of falls. When excessive, fear of falling can lead to a restriction or avoidance of activities and, consequently, to deconditioning, muscle atrophy, loss of postural control and reduced social participation. Factors associated with fear of falling in community-dwelling older adults in general have been investigated, however, little is known about the fear of falling in older adults with diabetes. In addition, no study has investigated the existence of differences in the factors associated with fear of falling between older adults with and without diabetes. Therefore, two cross-sectional analytic observational studies were conducted in order to fill the gaps in the literature about the factors related to fear of falling in diabetic older adults. The first study investigated the impact of the fear of falling on clinical, functional and gait variables in community-dwelling elderly women with type 2 diabetes mellitus and the variables that could predict the fear of falling in this population. Ninetynine diabetic older women were included, 49 with fear of falling (72.6 ± 6.1 years) and 50 without fear of falling (71.8 ± 4.8 years). Clinical variables included age, body mass index, waist-to-hip ratio, number of diseases and medications, physical activity level, history of falls, frailty level, cognition, depressive symptoms, fasting blood glucose and time since diabetes diagnosis. Functional variables included the performance on the Timed Up and Go test (TUG), sit-to-stand test and handgrip strength. Gait parameters were obtained using the GAITRite® system and included velocity, cadence, step length, step time, swing time, stance time and double support time, in addition to the variability measures. The group with fear of falling showed a higher frequency of frail individuals, more depressive symptoms, worse performance on the TUG and sit-to-stand test, lower gait velocity, cadence and step length and increased step time and swing time variability compared to the group without fear of falling (p < 0.05). In addition, logistic regression analysis showed that the Geriatric Depression Scale with 15 items (OR = 1.34; 95%CI = 1.11-1.61) and the TUG (OR = 1.36; 95%CI = 1.07-1.73) were predictors of fear of falling in community-dwelling diabetic older women. Thus, these instruments should be considered during the evaluation of diabetic older women with fear of falling. The second study aimed to determine among several sociodemographic, clinical (chronic diseases and health-related variables) and functional factors, which could be associated with fear of falling in community-dwelling older adults with and without diabetes mellitus. In this study, data from 4,449 older adults aged 65 years or older (19.2% with diabetes), resulting from a multicenter, multidisciplinary and epidemiological study named the Frailty in Brazilian Older People Study (FIBRA Network), were analyzed. Sociodemographic data included sex, age, marital status, educational level and living alone. The self-reported chronic diseases diagnosed by a physician within the last year included diabetes, cardiac disease (angina, myocardial infarction or heart attack), hypertension, stroke or cerebral ischemia, arthritis or rheumatism, pulmonary disease (bronchitis or emphysema), depression and osteoporosis, in addition to the total number of diseases. The health-related variables included the number of medications used regularly in the last three months, hearing and visual impairment, health self-perception, fall history in the previous 12 months, cognitive status, body mass index, depressive symptoms and frailty level. The functional capacity measures included the Katz Index, which assesses the basic activities of daily living, Lawton Scale, which assesses the instrumental activities of daily living, handgrip strength and gait speed test. The results of logistic regression analysis showed that the factors independently associated with fear of falling in non-diabetic older adults were female gender (OR = 1.69; 95%CI = 1.36-2.11), arthritis or rheumatism (OR = 1.33; 95%CI = 1.10-1.60), depression (OR = 1.55; 95%CI = 1.22-1.96), visual impairment (OR = 1.18; 95%CI = 1.01-1.39), negative health self-perception (OR = 1.56; 95%CI = 1.33-1.84), falls in the previous 12 months (OR = 1.35; 95%CI = 1.13-1.61), obesity (OR = 1.28; 95%CI = 1.02-1.61), depressive symptoms (OR = 1.28; 95%CI = 1.02-1.61), frailty (OR = 1.79; 95%CI = 1.18-2.71), Katz Index (OR = 1.42; 95%CI = 1.11-1.80), Lawton Scale (OR = 0.87; 95%CI = 0.84-0.91), handgrip strength (OR = 0.97; 95%CI = 0.96-0.99) and gait speed test (OR = 0.33; 95%CI = 0.24-0.46). On the other hand, the factors associated with fear of falling in diabetic older adults were female gender (OR = 1.93; 95%CI = 1.36-2.75), arthritis or rheumatism (OR = 1.61; 95%CI = 1.13-2.29), negative health self-perception (OR = 1.77; 95%CI = 1.27-2.46), Mini-Mental State Examination (OR = 0.95; 95%CI = 0.90-0.99), frailty (OR = 2.31; 95%CI = 1.14-4.67), Lawton Scale (OR = 0.85; 95%CI = 0.78-0.93) and gait speed test (OR = 0.41; 95%CI = 0.22- 0.79). Therefore, the factors associated with fear of falling differ between older adults with and without diabetes mellitus. Such differences should be considered by health care professionals in the planning of their therapeutic approaches for a successful management of fear of falling in these populations.